Assessment of Post Harvest Losses in Banana Grown in Gujarat - P R Davara (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2009)
The present investigation was undertaken to assess post harvest losses (at field, traders' and processors' level) in Gujarat. The effect of various ripening methods on post harvest losses in five varieties viz., Robusta, Grande Naine, Sona, Mahalaxmi and Shreemanthi were determined. The study revealed that overall post harvest loss in banana after harvesting till ripening was found to be 15.43%, which included losses at field level (0.77%), at trader's level comprising of transportation and handling losses (5.86%) as well as ripening losses (8.80%). Only negligible losses were observed during processing of banana. The highest loss (16.00%) was observed in the case of smoking + room temperature method of ripening, while the lowest (4.66%) was observed under ethephon + air-cooled chamber method. Ethephon + ice treatment method resulted in ripening loss to the tune of 7.43%, but the method was most widely adopted in Gujarat owing to its convenience and better appearance of bananas after ripening.